2018
DOI: 10.1111/ajpy.12207
|View full text |Cite
|
Sign up to set email alerts
|

Does accuracy and confidence in working memory performance relate to academic achievement in NAPLAN, the Australian national curriculum assessment?

Abstract: Objective: The aim of this study was to examine how accuracy and confidence in working memory performance relates to academic achievement as assessed in the Australian national curriculum assessment (National Assessment Program-Literacy and Numeracy (NAPLAN)). Method: A total of 150 Australian schoolchildren enrolled in Year 4 participated in the study. Accuracy and confidence in performance of a working memory task were assessed. Associations between these working memory measurements and scores in each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Future research on the topic should focus on more types of executive functions or cognitive mechanisms which might be restored by exposure to nature. This study primarily focused on working memory, which in turn could be associated with higher academic performance [28,29]. When future research would find more cognitive components which may benefit from observing nature, the implication of nature in academic setting would become more powerful and desirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research on the topic should focus on more types of executive functions or cognitive mechanisms which might be restored by exposure to nature. This study primarily focused on working memory, which in turn could be associated with higher academic performance [28,29]. When future research would find more cognitive components which may benefit from observing nature, the implication of nature in academic setting would become more powerful and desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Even when controlling for intelligence, different executive functions could positively predict academic performance [27]. Focusing on the executive function of working memory, Chalmers and Freeman [28] showed that performance on a working memory task was positively associated with the NAPLAN, an Australian national curriculum assessment in children just under 10 years old. Another study by Rhodes et al [29] revealed a positive correlation between working memory and performance in chemistry in early high school children.…”
Section: Art Ef and Academic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Working memory is required in almost all everyday tasks such as remembering the order of steps required to complete a task, linking letters together to form words, solving math problems, linking words together to enable comprehension, locating oneself in space, reading maps, and so forth. Working memory has been linked to numerous areas of child development including academic achievement [ 35 , 36 , 37 ] and intelligence [ 38 , 39 ]. Working-memory difficulties have also been associated with classroom behaviour problems [ 40 ].…”
Section: Introductionmentioning
confidence: 99%